Paraoxonase (PON1) L55M and Q192R polymorphisms in major depression and bipolar affective disorder - YILDIZ, MESUT (UNIV SAO PAULO, INST PSIQUIATRIA, 2017)
Background: Oxidative and nitrosative stress pathways, along with immune-inflammatory response, might play an important role in the pathogenic mechanisms underlying major depression and bipolar disorder. Objective: The aim of the present study is to investigate paraoxonase 1 polymorphisms and its correlations with disease parameters in patients with major depression and bipolar affective disorder. Methods: PON1 L55M and Q192R single nucleotide polymorphisms were analyzed in a group consisted of 100 patients with major depression, and 100 patients with bipolar affective disorder and 96 healthy controls. Polymorphisms were analyzed by using polymerase chain reaction. Results: Our findings reported no association between Q192R and L55M polymorphisms of PON1 and major depression and bipolar disorder. Additionally, there was no association between the PON1 genotypes and disease variables in both depressed and bipolar patients. Discussion: Evaluating the different stages of patients with affective disorders and and investigating the connection between PON1 polymorphisms and treatment outcomes will help us to clarify the relationship between PON1 and mood disorders.
Keywords: Major depression; bipolar affective disorder; paraoxonase (PON1); polymorphism; association study; GENOME-WIDE ASSOCIATION; SERUM PARAOXONASE; (PON)1 ACTIVITY; ARYLESTERASE; GENE; POPULATION; STRESS; HEALTH; RISK